Effect of nitric oxide on the sinusoidal uptake of organic cations and anions by isolated hepatocytes - Song, Im -Sook; Lee, In -Kyoung; Chung, Suk -Jae; Kim, Sang -Geon; Lee, Myung -Gull; Shim, Chang -Koo (Archives of pharmacal research, 2002)
The issue of whether or not the presence NOx (NO and oxidized metabolites) in the hepatocytes at pathological levels affects the functional activity of transport systems within the sinusoidal membrane was investigated. For this purpose, the effect of the pretreatment of isolated hepatocytes with sodium nitroprusside (SNIP), a spontaneous NO donor, on the sinusoidal uptake of tributylmethylammonium (TBuMA) and triethylmethyl ammonium (TEMA), representative substrates of the organic cation transporter (OCT), and taurocholate, a representative substrate of the Na⁺/taurocholate cotransporting polypeptide (NTCP), was measured. The uptake of TBuMA and TEMA was not affected by the pretreatment, as demonstrated by the nearly identical kinetic parameters for the uptake (i.e., Vₘₐₓ, Kₘ and CLₗᵢₙₑₐᵣ). The uptake of mannitol into hepatocytes was not affected, demonstrating that the membrane integrity remained constant, irregardless of the SNP pretreatment. On the contrary, the uptake of taurocholate was significantly inhibited by the pretreatment, resulting in a significant decrease in Vₘₐₓ, thus providing a clear demonstration that NOx preferentially affects the function of NTCP rather than OCT on the sinusoidal membrane. A direct interaction between NOx and NTCP or a decrease in Na⁺/K⁺ ATPase activity as the result of SNP pretreatment might be responsible for this selective effect of NOx.